Historical ecology identifies long‐term rewilding strategy for conserving Mediterranean mountain forests in south Italy. Issue 2 (19th December 2022) - Palli, Jordan; Mensing, Scott A.; Schoolman, Edward M.; Solano, Francesco; Piovesan, Gianluca
Abstract: In the context of global decline in old‐growth forest, historical ecology is a valuable tool to derive insights into vegetation legacies and dynamics and develop new conservation and restoration strategies. In this cross‐disciplinary study, we integrate palynology (Lago del Pesce record), history, dendrochronology, and historical and contemporary land cover maps to assess drivers of vegetation change over the last millennium in a Mediterranean mountain forest (Pollino National Park, southern Italy) and discuss implications in conservation ecology. The study site hosts a remnant beech–fir ( Fagus sylvatica – Abies alba ) mixed forest, a priority habitat for biodiversity conservation in Europe. In the 10th century, the pollen record showed an open environment that was quickly colonized by silver fir when sociopolitical instabilities reduced anthropogenic pressures in mountain forests. The highest forest cover and biomass was reached between the 14th and the 17th centuries following land abandonment due to recurring plague pandemics. This rewilding process is also reflected in the recruitment history of Bosnian pine ( Pinus heldreichii ) in the subalpine elevation belt. Our results show that human impacts have been one of the main drivers of silver fir population contraction in the last centuries in the Mediterranean, and that the removal of direct human pressure led to ecosystem renovation. Since 1910, the Rubbio State Forest has locally protected and restored the mixed beech–fir forest. The institutions in 1972 for the Rubbio Natural Reserve and in 1993 for Pollino National Park have guaranteed the survival of the silver fir population, demonstrating the effectiveness of targeted conservation and restoration policies despite a warming climate. Monitoring silver fir populations can measure the effectiveness of conservation measures. In the last decades, the abandonment of rural environments (rewilding) along the mountains of southern Italy has reduced the pressure on ecosystems, thus boosting forest expansion. However, after four decades of natural regeneration and increasing biomass, pollen influx and forest composition are still far from the natural attributes of the medieval forest ecosystem. We conclude that long‐term forest planning encouraging limited direct human disturbance will lead toward rewilding and renovation of carbon‐rich and highly biodiverse Mediterranean old‐growth forests, which will be more resistant and resilient to future climate change.